Field report PAC 671: Schlumberger / Nur Farah Nisa Ahmad Fauzi - Ahmad Fauzi, Nur Farah Nisa (Universiti Teknologi MARA, Terengganu, 2024)
Since Conrad and Marcel Schlumberger founded it in 1926, Schlumberger has been a trailblazer in transforming the oil and gas sector. Originating from the brothers' vision to utilize electrical measurements for understanding subsurface formations, the company has consistently pushed technological boundaries in oilfield services. Today, with operations spanning across more than 120 countries and a workforce of around 100,000 employees, Schlumberger stands as a global leader. It offers a comprehensive range of services including technology solutions, integrated project management, and information services crucial for the oil and gas industry. Its diverse portfolio covers exploration, drilling, reservoir characterization, production, and processing, underscoring its pivotal role in the sector's evolution.